PULMONOLOGIST’S SATISFACTION WITH THE USE OF I-GEL LARYNGEAL MASK AIRWAY (LMA) FOR BRONCHOSCOPY IN DR. WAHIDIN SUDIROHUSODO MAKASSAR CENTRAL GENERAL HOSPITAL - Juliansyah, Juliansyah; Nurdin, Haizah; Arif, Syafri Kamsul; Salam, Syamsul Hilal; Ratnawati, Ratnawati; Palinrungi, Ari Santri (E-Jurnal Medika Udayana, 2024)
Bronchoscopy is a type of endoscope used to examine internal organs in the body. This examination is performed by competent physicians, by examining the bronchi or the branches for diagnostic or therapeutic purposes. The use of the LMA for airway management during Fiberoptic Flexible Bronchoscopy (FFB) was first introduced in 1989 and was described as a safe and favorable tool for airway control during bronchoscopy in both adult and pediatric populations. The advantage of an LMA over an endotracheal tube is that it is equipped with a larger diameter tube, allowing for better visibility and flexibility. The I-gel LMA is the most frequently used type of LMA. This study aimed to determine the satisfaction of pulmonologists with the use of LMA I-gel when performing bronchoscopy in Dr. Wahidin Sudirohusodo Central General Hospital Makassar. The research employed probability sampling with an experimental design, using questionnaires for data collection. There were 36 patients underwent bronchoscopy from June ? December 2023. Demographic data were collected (age, sex, body mass index, and American Society of Anesthesiologists physical status), assessment based on the first successful attempt of fiberoptic insertion with a value of p = 0,06, quality of visualization, flexibility of the scope, size of the fiberoptic that can be used, and limitations of performance during bronchoscopy with a value of p < 0,05. It was found that pulmonologists were satisfied with the use of I-gel LMA during bronchoscopy. However, this result was also influenced by the experience of pulmonologists in performing the procedure. Keywords: Bronchoscopy, LMA I-gel, Satisfaction